The impact of using artificial intelligence techniques in improving the quality of educational services/case study at the University of Baghdad - Farhan, Neamah Dahash; Sadiq, Bareq Habeeb; Zwayyer, Mustafa H.; Arnout, Boshra A. (Frontiers in Education, 2024)
The utilization of artificial intelligence techniques has garnered significant interest in recent research due to their pivotal role in enhancing the quality of educational offerings. This study investigated the impact of employing artificial intelligence techniques on improving the quality of educational services, as perceived by students enrolled in the College of Pharmacy at the University of Baghdad. The study sample comprised 379 male and female students. A descriptive-analytical approach was used, with a questionnaire as the primary tool for data collection. The findings indicated that the application of artificial intelligence methods was highly effective, and the educational services provided to students were of exceptional quality. The results also showed a strong correlation (correlation coefficient of 0.719) between the use of artificial intelligence techniques and the quality of educational services. This correlation was statistically significant at a confidence level of 99%. The impact of artificial intelligence techniques and their dimensions on the quality of educational services is highly significant at a confidence level of 99%. This suggests that artificial intelligence technologies play a major role in enhancing the quality of educational services. The study emphasizes the importance of creating technologically advanced classrooms equipped with modern devices and equipment to enhance the learning experience and provide an advanced educational environment. It also highlights the significance of effectively addressing students’ complaints and grievances through technical means, such as electronic communication platforms, social media platforms, technical support via the Internet, and smartphone applications. These measures are essential in providing high-quality educational services.